A critical approach proposal for training translation memory systems in translator education programs - Andrade Stupiello, Erika Nogueira de [UNESP]; Esqueda, Marileide Dias (John Benjamins Publishing Co, 2016)
The fast pace of todays translation market and the definite integration of translation memory systems TMS in the translators workstation have created new demands in terms of technological skills expected from novice translators. Aiming to prepare future translators to meet market demands, many translation undergraduate programs in Brazil have included the training on translation memory systems in their curricula. Applying the action-research methodology, this paper reports on the training methodology used for TMS in translation classrooms at two Brazilian public universities. The collected data in both contexts suggest that TMS may affect both the composing of the final translation and the decision-making of trainee translators and the quality of their production if they do not reflectively challenge their choices and the suggested output.